Gerakan Literasi Budaya di Keluarga: Penelitian - Muhammad Nawir; Hikmah Idris; Husnul Khatimah; Sarmila (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
A Family is the first and main place of education for children. In the family, children learn from the womb until the child's journey into their own household. Therefore, the family has a very basic role in optimizing all the potential of the child. The family literacy movement is based on the desire to improve the literacy skills of family members. herefore, the understanding of literacy as the ability to identify information needs, search for, obtain, process, and re-inform information needs to be improved in the family realm. To improve these literacy skills, the role of the family is very important. The family as the smallest unit in society, in the context of education, becomes the first and main learning environment for children. Through daily activities, parents or family members can introduce children to traditional music (such as gamelan, angklung, and sasando), regional dances, and folk songs. For example, parents sing regional songs as a lullaby or take children to watch traditional art performances. Parents must be able to find solutions and be as creative as possible in finding ways to be able to realize a literate family that can become a generation of national pride. Smart, creative, and caring parents will be very capable of realizing a culture of literacy in the family.